PROCESS VALIDATION AND REGULATORY REQUIREMENTS OF METERED-DOSE INHALERS: AN OVERVIEW - Sunil, Ashrani; Anju, Goyal; Rajat, Vaishnav (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The goal of the validation is to assure that quality is built into the system at every step, and not just tested for at the end. The validation activities will commonly include training on production material and operating procedures, training of people involved, and monitoring of the system while in production. Each and every doses form needs to be validated to reduce the chances of batch failures and market recalls. In case of metered-dose inhalers (MDIs) also it becomes mandatory. US Food and Drug Administration defines process validation as establishing documented evidence which provides a high degree of assurance that a specific process will consistently produce a product meeting its predetermined specifications and quality characteristics.â€ MDIs are known as device that is made to deliver a specific amount of aerosolized medication in the form of short burst directly to the lungs when inhaled by the patient. Furthermore, the inhalational drug delivery causes less pain and is convenient for administration. The patients of asthma, emphysema, and chronic obstructive pulmonary disease are prescribed for quicker relief. The present paper is a summary of process involved in the manufacturing of MDIs and focuses on the regulatory requirements along with their process validation.